Groundwater Quality Assessment Based on Water Quality Index in Northern Cyprus - Kassem, Y.; Gökçekuş, H.; Rizza, T. (Engineering, Technology & Applied Science Research, 2022)
The largest coastal aquifer in northwestern Cyprus is the Morphou aquifer. The objective of the current study was to evaluate the quality of the groundwater and its suitability for drinking purposes in the Morphou (Güzelyurt) region, Cyprus. To realize this aim, 118 groundwater samples were collected during wet and dry seasons over a period of 11 years. Major physicochemical characteristics (electrical conductivity, pH, bicarbonate, calcium, magnesium, chloride, and total and carbonate hardness) were measured and analyzed. The assessment of groundwater quality was evaluated with the help of the Water Quality Index (WQI). The results demonstrated that 56% and 50% of the groundwater samples during dry and wet seasons respectively were unsatisfactory according to the Cl- limits of the WHO standard. In addition, approximately 10% of the groundwater samples come under class 2 (good water), 30% of the samples come under class 3 (fairwater), 13% come under classes 4 and 5, and the rest under class 6 (unsuitable for drinking).